Effectiveness of insulin infusion therapy for hypertriglyceridemia-induced acute pancreatitis - Vu, Thi Minh Tam; Ma, Phuoc Nguyen; Ho, Tan Phat; Tran, Van Huy (Tạp chí Y Dược Huế, 2025)
Background: Hypertriglyceridemia (HTG) is an increasingly recognized cause of acute pancreatitis (AP) in Vietnam. Despite its clinical relevance, there are currently no universally accepted guidelines for the use of insulin in the management of HTG-induced acute pancreatitis (HTG-AP). Furthermore, existing evidence on the efficacy and safety of insulin therapy in this setting remains limited. Objective: This study aimed to assess treatment outcomes and safety of insulin infusion therapy in mild and moderately severe HTG-AP. Methods: Observational study of therapeutic effectiveness, 93 patients with mild and moderately severe HTG-AP treated at the Department of Gastroenterology, Cho Ray Hospital from August 2023 to June 2024 were enrolled. Results: Mean value of TG levels decreased rapidly from 4348.4 mg/dL at admission to 1227.3 mg/dL after 48 hours and 747.5 mg/dL after 72 hours of insulin infusion therapy (p<0.05). The rates of achieving TG < 500 mg/dL after 48 hours and 72 hours were 34.4% and 52.7%, respectively. Pain relief rates were 28.0% after 48 hours and 63.4% after 72 hours. Mean time to achieve pain relief and fasting was 3.2 days; the average length of hospital stay was 6.2 days. All patients fully recovered and were discharged with no mortality or severe adverse events. Patients with TG > 2000 mg/dL had longer TG reduction time (3.4 vs 2.0 days) and hospitalization (7.1 vs 5.9 days; p<0.05). Mild hypokalemia was observed in most patients (95.7%). Conclusion: Insulin infusion therapy appeared a safe and effective treatment in patients with mild and moderately-severe HTG-AP.